Psychological Inflexibility in Pain Scale – Portuguese version (PIPS-PT). (Wicksell, Lekander, Sorjonen, & Olsson, 2010). - Galhardo, Ana (2019)
The PIPS Portuguese version (PIPS-PT) was studied in a sample of 209 women presenting a diagnosis of endometriosis. This self-report instrument assesses psychological inflexibility associated with chronic pain. In the Portuguese version the two-factor structure was replicated: (1) pain avoidance and (2) cognitive fusion, and this model showed a good fit. Regarding internal consistency, a Cronbach alpha of .94 was found for the total score, of .94 for the pain avoidance subscale and of .82 for the cognitive fusion subscale. anagalhardo@ismt.pt